Scrutinizing the Reasons for Using First Language in EFL Classrooms - Dea Silvani; Tia Pertama (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
Using first language in the English class remains a controversial and an interesting issue to investigate, since it becomes an inevitable phenomenon especially in EFL contexts. Thus, this present study aims to investigate the underlying reasons for using L1 by both students and teacher in the EFL classrooms. In this case study, semi-structured interview was used to collect the data from the teacher and the students related to the reasons of using L1 in EFL classrooms. Thematic Analysis (Braun Clarke, 2006) was used to analyze the data. The research results showed that the teachers generally used L1 because they believed that it supported the effective process of language teaching, since it can avoid students’ confusion over the materials being discussed, and it can make the students feel more comfortable in joining teaching and learning process. Meanwhile, the students used L1 mostly because of their natural habit, lack of confidence, and fear of making mistakes due to their low proficiency level in using English. Additionally, they also consider that using L1 was easier to communicate their ideas. In conclusion, L1 plays some supportive roles in English class. However, its use must be re-examined, since it should be used appropriately to achieve the better learning outcomes.